Tai Chi Quan Versus Physical Therapy on Pain and Cognitive Performance for Elderly People With Chronic Low Back Pain: Study Protocol for a Randomized Controlled Trial - Wang, Rui; Zhu, Dong; Wang, Lin; Liu, Jing; Zou, Jun; Sun, Yang; Jiang, Yan; Hu, Hao-Yu; Deng, Zhi-Wei; Weng, Lin-Man; Zheng, Kang-Yong; Kiartivich, Suparata; et al. (Frontiers in Aging Neuroscience, 2022)
Objectives: Chronic low back pain has become a major cause of global disability and caused a huge economic burden to society. Physical therapy is a vital strategy for rehabilitation of chronic low back pain. Although several trials have shown that Tai Chi Quan is a beneficial treatment, the comparative effectiveness of Tai Chi Quan versus physical therapy is unknown. We are conducting a randomized controlled trial to assess the effectiveness of Tai Chi Quan versus that of physical therapy in treating chronic low back pain. Methods: We will perform a single-blind randomized controlled trial on elderly people with chronic low back pain. 138 participants will be randomly assigned to the Tai Chi Quan group (60-minute classes, three times per week for 12 weeks) or physical therapy group (10 minutes of evaluation and warm-up, 40 minutes of therapist-directed exercise therapy, and 10 minutes of relaxation, three times per week for 12 weeks) with an allocation of 1:1. The participants will be followed up for 40 weeks for the study of long-term effects. The primary outcomes include pain intensity and back-related function at 12 weeks. Secondary outcomes include lumbar quantitative sensory testing, balance, cognitive function, psychosocial function, cost-effectiveness, compliance and adverse events. We will perform the intention-to-treat analysis for withdrawal and missing data. Discussion: The study will be the first randomized trial with comparative-effectiveness of Tai Chi Quan and physical therapy for chronic low back pain. Standardized protocol, large sample size, and comprehensive outcomes are important features in this trial. This study aims to determine the feasibility and effectiveness of Tai Chi Quan for low back pain. The results of this study will be beneficial for elderly people with low back pain and medical rehabilitation personnel. Trial registration: Chinese clinical trial registry, ChiCTR2000029723.